A Brief History of War Amputation. Issue 4 (1st December 2011) - Kinch, Kevin; Clasper, JC
Abstract : Throughout the history of warfare, changes in weaponry have produced changes in the nature of war injury. The 16th century saw the introduction of firearms in conventional warfare, bringing the destructive power of weaponry to new and unseen heights with a dramatic increase in the severity and complexity of battle injuries. Destructive gunshot wounding associated with embedded foreign material often led to sepsis and demanded the more radical treatment of amputation. Over the past 500 years innumerable developments have taken place in anaesthesia, asepsis, transfusion therapy and resuscitation, antibiotic therapy, vascular surgery and wound management. Medical services have had to adapt in order to cope with the changing volume and changing nature of battle casualties resulting from modern weaponry. Despite the progress made, amputation is still a commonly performed operation following traumatic limb injury. In those cases where the decision to amputate is not so clearly and distinctly defined, history has shown that prevention of infection requires aggressive primary surgery and removal of all devitalised tissue. This paper examines the history of amputation in the management of the battlefield casualty suffering limb injury, beginning in the 16th century and continuing into present day.